Preferential CO2 Separation Over Nitrogen by a Free-standing and Nanometer-thick Membrane. (July 2017) - Fujikawa, Shigenori; Ariyoshi, Miho; Shigyo, Eiko; Fukakusa, Chihoko; Roman, Selyanchyn; Kunitake, Toyoki
Abstract: Membrane thinning is important approach to enhance gas permeation properties of CO2 capture membranes. We employed cross linkable polymer materials, conventional epoxy resin containing amino groups, for the preparation of free-standing and ultrathin nanomembrane. By simple spincoating, nanometer-thick epoxy membranes were fabricated and detached as a free-standing membrane. The thickness of a membrane was readily controllable by spincoating speed and polymer concentration. Although as-prepared nanomembrane did not show CO2 selectivity over N2, wet membrane shows high CO2 selectively. Further sophistication of membrane material design and reduction of membrane thickness would be a promising approach to prepare preferential CO2 separation membrane with high gas flux.